Non-Isothermal Modeling of Dark Current-Voltage Measurements of a CIGS Solar Cell. (1st January 2018) - Obradović, Ana; Toch, Kenneth; Coppens, Bert; Khelifi, Samira; Lauwaert, Johan; Thybaut, Joris
Abstract : Dark current density-voltage measurements were performed in a temperature range 110–290 K in both forward and reverse bias on a 0.5 cm 2 solar cell sample to determine current and voltage losses in a CIGS solar cell. For the first time a JD − V model applicable in a wide temperature range was constructed by adding non-ideality terms to the Shockley diode equation and comparing the experimentally acquired data to the model simulation results. The shunt current was modeled assuming space charge limited current by a uniform distribution of trap levels. A total of only 9 adjustable parameters in the final JD − V model sufficed to simulate all experimental data simultaneously, i.e., no re-estimation had to be performed at different temperature levels. The estimates for the diode ideality factor n = 1.8 and the diode activation energy ΔE = 1.20 eV coincide with values typically obtained for CIGS solar cell dominated by recombination in the absorber. The quality of the CIGS solar cell used in this study was also confirmed by the low back contact activation barrier of 52 meV and the high shunt resistance. We demonstrate that this flexible model can be used to make an initial prediction of the resistive losses and non-idealities in thin film solar cells.